Do they stay or go? Analysis of international students in Finland. (27th May 2021) - Mathies, Charles; Karhunen, Hannu
ABSTRACT: The increase in international student mobility raises questions of how many international students choose to stay in their host country and the reasons why some stay and others leave. This study examines factors affecting international students to stay in Finland three years after graduation. Tracking 13 (years) graduating cohorts across national (Finland) data registries, we find family ties and labour market opportunities relate to an increased probability an international student stays in Finland three years after graduation.